Nihil est sine sono (1. Kor. 14,10). Musik in interkulturellen Begegnungen. Reinhold Bernhardt / Verena Grüter (Hg.): Musik in interreligiösen Begegnungen, TVZ Zürich 2019, 216 S - Schroeter-Wittke, Harald (Praktische Theologie)

4. Sonntag nach Trinitatis (27.6.2021). Gen 50,15-21: Diplomatische Wahrheit oder : Am Ziel der Träume – alles anders - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Das besondere Buch. Ralf Koerrenz und Tobias Nicklas (Hg.): Bildung. Jahrbuch für Biblische Theologie 35, Göttingen 2021 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Probing the Interactions of Immobilized Ruthenium Dihydride Complexes with Metal Oxide Surfaces by MAS NMR: Effects on CO2 Hydrogenation - Nguyen, Hoang-Huy; Li, Zheng; Enenkel, Toni; Hildebrand, Joachim; Bauer, Matthias; Dyballa, Michael; Estes, Deven P. (The Journal of Physical Chemistry C)
Homogeneous catalysts immobilized on metal oxides often have different catalytic properties than in homogeneous solution. This can be either activating or deactivating and is often attributed to interactions of catalyst species with the metal oxide surface. However, few studies have ever demonstrated the effect that close associations of active sites with surfaces have on the catalytic activity. In this paper, we immobilize H2Ru(PPh3)2(Ph2P)2N–C3H6–Si(OEt)3 (3) on SiO2, Al2O3, and ZnO and interrogate the relationship to the surface using IR, MAS NMR, 1H–31P HETCOR, and XAS spectroscopies. We found that while there are close contacts between the P atoms of the complex and all three metal oxide surfaces, the Ru–H bond only reacts with oxygen bridges on SiO2 and Al2O3, forming new Ru–O bonds. In contrast, complex 3 stays intact on ZnO. Comparison of the catalytic activities of our immobilized species for CO2 hydrogenation to ethyl formate showed that Lewis acidic metal oxides activate, rather than deactivate, complex 3 in the order Al2O3 > ZnO > SiO2. The Lewis acidic sites on the metal oxide surfaces most likely increase the productivity by increasing the rate of esterification of formate intermediates.
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Olefin Metathesis in Confinement: Towards Covalent Organic Framework Scaffolds for Increased Macrocyclization Selectivity - Emmerling, Sebastian T.; Ziegler, Felix; Fischer, Felix R.; Schoch, Roland; Bauer, Matthias; Plietker, Bernd; Buchmeiser, Michael R.; Lotsch, Bettina V. (Chemistry – A European Journal)
Covalent organic frameworks (COFs) offer vast structural and chemical diversity enabling a wide and growing range of applications. While COFs are well-established as heterogeneous catalysts, so far, their high and ordered porosity has scarcely been utilized to its full potential when it comes to spatially confined reactions in COF pores to alter the outcome of reactions. Here, we present a highly porous and crystalline, large-pore COF as catalytic support in α,ω-diene ring-closing metathesis reactions, leading to increased macrocyclization selectivity. COF pore-wall modification by immobilization of a Grubbs-Hoveyda-type catalyst via a mild silylation reaction provides a molecularly precise heterogeneous olefin metathesis catalyst. An increased macro(mono)cyclization (MMC) selectivity over oligomerization (O) for the heterogeneous COF-catalyst (MMC:O=1.35) of up to 51 % compared to the homogeneous catalyst (MMC:O=0.90) was observed along with a substrate-size dependency in selectivity, pointing to diffusion limitations induced by the pore confinement.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Higher MLCT lifetime of carbene iron(ii) complexes by chelate ring expansion - Reuter, Thomas; Kruse, Ayla; Schoch, Roland; Lochbrunner, Stefan; Bauer, Matthias; Heinze, Katja (Chemical Communications)
Combining strong σ-donating N-heterocyclic carbene ligands and π-accepting pyridine ligands with a high octahedricity in rigid iron(II) complexes increases the 3MLCT lifetime from 0.15 ps in the prototypical [Fe(tpy)2]2+ complex to 9.2 ps in [Fe(dpmi)2]2+12+. The tripodal CNN ligand dpmi (di(pyridine-2-yl)(3-methylimidazol-2-yl)methane) forms six-membered chelate rings with the iron(II) centre leading to close to 90° bite angles and enhanced iron-ligand orbital overlap
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Photoactive iron complexes: more sustainable, but still a challenge - Dierks, Philipp; Vukadinovic, Yannik; Bauer, Matthias (Inorganic Chemistry Frontiers)
On transition metals such as iron rests lots of hope to replace precious metal catalysts in the field of photochemistry for a more sustainable future. Indeed, significant progress has been made in recent years in terms of lifetime extension and emerging applications in catalysis. For this reason, recent synthetic strategies of new photoactive iron compounds, which have proved to show particularly promising properties, are reviewed here. The lifetime of the excited state serves as a key parameter for comparison with the standard ruthenium complex, [Ru(bpy)3]2+, to discuss the potential and performance of the iron complexes. This approach is complemented by a more holistic examination of the sustainability of such a substitution strategy in order to answer the question: when or at which point can we assume that iron represents a more sustainable alternative for noble metals in photochemical applications?
Keywords: Inorganic Chemistry

Selective Benzylic CH‐Borylations by Tandem Cobalt Catalysis - Ghosh, Pradip; Schoch, Roland; Bauer, Matthias; Jacobi von Wangelin, Axel (Angewandte Chemie International Edition)
Metal-catalyzed C−H activations are environmentally and economically attractive synthetic strategies for the construction of functional molecules as they obviate the need for pre-functionalized substrates and minimize waste generation. Great challenges reside in the control of selectivities, the utilization of unbiased hydrocarbons, and the operation of atom-economical dehydrocoupling mechanisms. An especially mild borylation of benzylic CH bonds was developed with the ligand-free pre-catalyst Co[N(SiMe3)2]2 and the bench-stable and inexpensive borylation reagent B2pin2 that produces H2 as the only by-product. A full set of kinetic, spectroscopic, and preparative mechanistic studies are indicative of a tandem catalysis mechanism of CH-borylation and dehydrocoupling via molecular CoI catalysts.
Keywords: General Chemistry; Catalysis

Electrochemical Reduction and Oxidation of Ruddlesden–Popper-Type La2NiO3F2 within Fluoride-Ion Batteries - Wissel, Kerstin; Schoch, Roland; Vogel, Tobias; Donzelli, Manuel; Matveeva, Galina; Kolb, Ute; Bauer, Matthias; Slater, Peter R.; Clemens, Oliver (Chemistry of Materials)
Within this article, it is shown that an electrochemical defluorination and additional fluorination of Ruddlesden–Popper-type La2NiO3F2 is possible within all-solid-state fluoride-ion batteries. Structural changes within the reduced and oxidized phases have been examined by X-ray diffraction studies at different states of charging and discharging. The synthesis of the oxidized phase La2NiO3F2+x proved to be successful by structural analysis using both X-ray powder diffraction and automated electron diffraction tomography techniques. The structural reversibility on re-fluorinating and re-defluorinating is also demonstrated. Moreover, the influence of different sequences of consecutive reduction and oxidation steps on the formed phases has been investigated. The observed structural changes have been compared to changes in phases obtained via other topochemical modification approaches such as hydride-based reduction and oxidative fluorination using F2 gas, highlighting the potential of such electrochemical reactions as alternative synthesis routes. Furthermore, the electrochemical routes represent safe and controllable synthesis approaches for novel phases, which cannot be synthesized via other topochemical methods. Additionally, side reactions, occurring alongside the desired electrochemical reactions, have been addressed and the cycling performance has been studied.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

η 3 ‐Coordination and Functionalization of the 2‐Phosphaethynthiolate Anion at Lanthanum(III)** - Watt, Fabian A.; Burkhardt, Lukas; Schoch, Roland; Mitzinger, Stefan; Bauer, Matthias; Weigend, Florian; Goicoechea, Jose M.; Tambornino, Frank; Hohloch, Stephan (Angewandte Chemie International Edition)
We present the η3-coordination of the 2-phosphaethynthiolate anion in the complex (PN)2La(SCP) (2) [PN=N-(2-(diisopropylphosphanyl)-4-methylphenyl)-2,4,6-trimethylanilide)]. Structural comparison with dinuclear thiocyanate-bridged (PN)2La(μ-1,3-SCN)2La(PN)2 (3) and azide-bridged (PN)2La(μ-1,3-N3)2La(PN)2 (4) complexes indicates that the [SCP]− coordination mode is mainly governed by electronic, rather than steric factors. Quantum mechanical investigations reveal large contributions of the antibonding π*-orbital of the [SCP]− ligand to the LUMO of complex 2, rendering it the ideal precursor for the first functionalization of the [SCP]− anion. Complex 2 was therefore reacted with CAACs which induced a selective rearrangement of the [SCP]− ligand to form the first CAAC stabilized group 15–group 16 fulminate-type complexes (PN)2La{SPC(RCAAC)} (5 a,b, R=Ad, Me). A detailed reaction mechanism for the SCP-to-SPC isomerization is proposed based on DFT calculations.
Keywords: General Chemistry; Catalysis